2016
DOI: 10.7314/apjcp.2015.16.18.8365
|View full text |Cite
|
Sign up to set email alerts
|

Association between Shammah Use and Oral Leukoplakia-like Lesions among Adult Males in Dawan Valley, Yemen

Abstract: Background: Shammah is a traditional form of snuff dipping tobacco (a smokeless tobacco form) that is commonly used in Yemen. Oral mucosal changes due to the use of shammah can usually be observed in the mucosal surfaces that the product touches. The aim of this study was to determine the association between shammah use and oral leukoplakia-like lesions. Other associated factors were also determined. Materials and Methods: A cross sectional study was conducted on 346 randomly selected adult males. Multi-stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The odds of having OPMD/oral cancer in relation to shammah uses ranged from three to 39 times. One study reported that the odds of developing OPMD/oral cancer among current shammah users are 39‐fold (95% CI: 14‐105), while another study reported a 13‐fold increased risk among current shammah users (12.99; 95% CI: 6.34‐26.59) . The associated risk was relatively low among those that have quit shammah use and ranged from threefold (3.65; 95% CI: 1.40‐9.50) to 12‐fold (12.6; 95% CI: 3.3‐48.2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The odds of having OPMD/oral cancer in relation to shammah uses ranged from three to 39 times. One study reported that the odds of developing OPMD/oral cancer among current shammah users are 39‐fold (95% CI: 14‐105), while another study reported a 13‐fold increased risk among current shammah users (12.99; 95% CI: 6.34‐26.59) . The associated risk was relatively low among those that have quit shammah use and ranged from threefold (3.65; 95% CI: 1.40‐9.50) to 12‐fold (12.6; 95% CI: 3.3‐48.2).…”
Section: Resultsmentioning
confidence: 99%
“…The risk for shammah users to develop these lesions was 39 times (39; 95% CI: 14‐105) higher than non‐users. It was also noted that the associated risk of OPMD and/or oral cancer was higher among the current shammah users for current users (39; 95% CI: 14‐105 and 12.99; 95% CI: 6.34‐26.59) compared to those that have quit (12.6; 95% CI: 3.3‐48.2 and 3.65; 95% CI: 1.40‐9.50) …”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations